2018
DOI: 10.2138/am-2018-6524
|View full text |Cite
|
Sign up to set email alerts
|

Sn-Isotope Fractionation as a Record of Hydrothermal Redox Reactions

Abstract: This is a preprint, the final version is subject to change, of the American Mineralogist (MSA) Cite as Authors (Year) Title. American Mineralogist, in press.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(9 citation statements)
references
References 67 publications
0
9
0
Order By: Relevance
“…37 The equilibrium Sn isotope fractionation factors among various Sn-bearing phases provided in this study are crucial for interpreting the existing or future Sn isotope data. For example, Yao et al 14 reported the Sn isotope fractionations between cassiterite and stannite from four tin deposits and found that these deposits had similar Δ 124/116 Sn(cassiterite−stannite) values with an average value of 1.95‰, i.e., 1.49‰ for Δ 122/116 Sn(cassiterite−stannite). They interpreted that the measured ΔSn(cassiterite−stannite) was due to the redox reaction, i.e., from Sn(II) to Sn(IV) in hydrothermal fluids.…”
Section: Controlling Factors Of Sn Isotope Fractionationmentioning
confidence: 99%
See 1 more Smart Citation
“…37 The equilibrium Sn isotope fractionation factors among various Sn-bearing phases provided in this study are crucial for interpreting the existing or future Sn isotope data. For example, Yao et al 14 reported the Sn isotope fractionations between cassiterite and stannite from four tin deposits and found that these deposits had similar Δ 124/116 Sn(cassiterite−stannite) values with an average value of 1.95‰, i.e., 1.49‰ for Δ 122/116 Sn(cassiterite−stannite). They interpreted that the measured ΔSn(cassiterite−stannite) was due to the redox reaction, i.e., from Sn(II) to Sn(IV) in hydrothermal fluids.…”
Section: Controlling Factors Of Sn Isotope Fractionationmentioning
confidence: 99%
“…Thermodynamic equilibrium isotope fractionation among minerals is a powerful tool to understand numerous geological processes, such as mineralization, deep Earth, and planetary processes, and is key to understanding the fractionation mechanisms of emerging isotope systems. In this study, we focus on equilibrium Sn isotope fractionation among Sn-bearing minerals. Tin’s isotopes have become an emerging and rapid-growing isotope system in geochemistry research because of their unique roles in tracing various geological and cosmochemical processes such as ore-forming, magmatic differentiation, and evaporation/condensation and also in addressing archeological issues. In minerals, tin can occur in three oxidation states, i.e., +4 (e.g., cassiterite and stannite), +2 (e.g., romarchite and herzenbergite), and 0 (e.g., native tin) and coordinate with O (e.g., cassiterite and romarchite), S (e.g., stannite and herzenbergite), and Cl (e.g., panichiite and abhurite) . It has been found that the change of the Sn oxidation state can result in large Sn isotope fractionation among Sn-bearing minerals, but the effect of the coordination environment has only been investigated for aqueous and vaporous Sn species. The knowledge of equilibrium Sn isotope fractionation factors among minerals is the quantitative basis for understanding the fractionation mechanisms of Sn isotopes and investigating geological and cosmochemical processes using Sn isotopes.…”
Section: Introductionmentioning
confidence: 99%
“…In the process of transport and enrichment of tin in magmatic hydrothermal fluid, the change of redox condition is an important controlling factor of tin mineralization (Heinrich, 1990), and the Sn isotope investigation suggested that the variation of valance state is the main factor controlling the Sn isotope fractionation (Yao et al, 2018). In addition, Roskosz et al (2020) In addition, we also calculated the Sn isotope fractionation between Sn(II)−OH, Sn(II)−F, Sn(II)−SO 4 , Sn(II)−CO 3 species and Sn(IV)−Cl species.…”
Section: Tin Isotope Fractionation Caused By Valence Change Between S...mentioning
confidence: 99%
“…In recent years, with the rapid development of nontraditional isotope geochemistry, accurate determination of tin isotopic composition for geological samples has allowed us to use Sn isotope data to trace the process of tin mineralization (Badullovich et al, 2017;Mathur et al, 2017;Wang et al, 2019). The preliminary application of the Sn isotope in the study of hydrothermal tin mineralization shows that they can trace redox reactions that occurred during the formation of tin deposits (Brugger et al, 2016;Mason et al, 2016;Creech et al, 2017;Yao et al, 2018;She et al, 2020;Wang et al, 2021). Recent experiments by Wang et al (2019) suggested that vaporation-induced fractionation results in the residual solution becoming isotopically lighter, and heavier Sn isotopes are favored in a stronger bonding environment associated with oxidation.…”
Section: Introductionmentioning
confidence: 99%
“…9 Moreover, the Sn isotope ratios of cassiterite might also be used as a proxy in discriminating petrological sources and processes. 10 A measuring technique with high accuracy and precision is essential to detect variations of Sn isotope ratios in cassiterite. The pioneering study on the determination of Sn isotope ratios by De Laeter and Jeffery (1965, 1967) 1,11 applied thermal ionisation mass spectrometry (TIMS).…”
Section: Introductionmentioning
confidence: 99%